Planktonic Lipidome Responses to Aeolian Dust Input in Low-Biomass Oligotrophic Marine Mesocosms - Meador, Travis B.; Goldenstein, Nadine I.; Gogou, Alexandra; Herut, Barak; Psarra, Stella; Tsagaraki, Tatiana M.; Hinrichs, Kai-Uwe (Frontiers in Marine Science, 2017)
The effect and fate of dry atmospheric deposition on nutrient-starved plankton in the Eastern Mediterranean Sea (EMS; Crete, 2012) by spiking oligotrophic surface seawater mesocosms (3 m3) with Saharan dust (SD; 1.6 g L-1; 23 nmol NOx mg-1; 2.4 nmol PO4 mg-1) or mixed aerosols (A; 1.0 g L-1; 54 nmol NOx mg-1; 3.0 nmol PO4 mg-1) collected from natural and anthropogenic sources. Using high resolution liquid chromatography-mass spectrometry, the concentrations of over 350 individual lipids were measured in suspended particles to track variations in the lipidome associated with dust fertilization. Bacterial and eukaryotic intact polar lipid (IPL) biomarkers were categorized into 15 lipid classes based on headgroup identity, including four novel IPL headgroups. Bulk IPL concentrations and archaeal tetraether lipids were uncoupled with the doubling of chlorophyll concentrations that defined the stimulation response of oligotrophic plankton to SD or A amendment. However, molecular level analysis revealed the dynamics of the IPL pool, with significant additions or losses of specific IPLs following dust spikes that were consistent among treatment mesocosms. Multivariate redundancy analysis further demonstrated that distribution of IPL headgroups and molecular modifications within their alkyl chains were strongly correlated with the temporal evolution of the plankton community and cycling of phosphate. IPLs with phosphatidylcholine, betaine, and an alkylamine-like headgroup increased in the post-stimulated period, when phosphate turnover time had decreased by an order of magnitude and phosphorus uptake was dominated by plankton > 2 µm. For most IPL classes, spiking with SD or A yielded significant increases in the length and unsaturation of alkyl chains. A lack of corresponding shifts in the plankton community suggests that the biosynthesis of nitrogenous and phosphatidyl lipids may respond to physiological controls during episodic additions of dust to the EMS. Furthermore, alkyl chain distributions of IPLs containing N, P, and S invoked a bacterial source, suggesting that bacterioplankton are able to modulate these lipids in response to nutrient stress.